2014
DOI: 10.1007/s00415-014-7470-0
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase (NOX2) activity is a modifier of survival in ALS

Abstract: NADPH-oxidases (NOX) catalyze the formation of reactive oxygen species (ROS), which play a role in the development of neurological diseases, particularly those generated by the phagocytic isoform NOX2. Increased ROS has been observed in the amyotrophic lateral sclerosis (ALS) SOD1 transgenic mouse, and in this preclinical model the inactivation of NOX2 decreases ROS production and extends survival. Our aim was to evaluate NOX2 activity measuring neutrophil oxidative burst in a cohort of 83 ALS patients, and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…These astrocytes also expressed cleaved caspase-3 and NOX2. The NADPH-oxidase NOX2 generates ROS, which are known to induce oxidative stress and one of the modifiers of ALS disease [43, 44]. Therefore, these abnormally activated astrocytes are likely to be harmful to spinal motor neurons by generating ROS.…”
Section: Discussionmentioning
confidence: 99%
“…These astrocytes also expressed cleaved caspase-3 and NOX2. The NADPH-oxidase NOX2 generates ROS, which are known to induce oxidative stress and one of the modifiers of ALS disease [43, 44]. Therefore, these abnormally activated astrocytes are likely to be harmful to spinal motor neurons by generating ROS.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to ALS, the focus is more clearly on the therapeutic benefits of inactivation of NOX. For example, NOX2 activity in 83 ALS patients was assessed by measuring neutrophil oxidative burst in fresh blood samples by flow cytometry (Marrali et al ., ). Although the activity of the enzyme was independent of gender and disease duration, a lower NOX2 level correlated with a longer survival time from disease onset.…”
Section: Nox‐based Therapies In Neurodegenerative Diseasementioning
confidence: 97%
“…Based on the potential role of NOX enzymes in ALS pathology, it is reasonable to investigate whether targeting of NOX can be therapeutic. Studies investigating NOX’s role in human ALS patients found that patients that had lower NOX2 activity in their peripheral blood cells showed significant increases in survival [275]. Additionally, ALS mice deficient in NOX2 showed decreased oxidative stress in spinal cords and a modest increase in lifespan (Table 2) [262].…”
Section: Introductionmentioning
confidence: 99%